Reproductive physiology of Rhamdia quelen is improved by dietary inclusion of probiotics - Lins Rodrigues, Mariana; Damasceno, Danielle Zanerato; Marques Gomes, Ricácio Luan [UNESP]; Sosa, Bruno dos Santos [UNESP]; Moro, Evandro Bilha [UNESP]; Sanches, Eduardo Antônio [UNESP]; Bittencourt, Fábio; Signor, Altevir (Hindawi, 2021)
This study evaluated the effects of a probiotic additive on reproductive variables of the silver catfish (Rhamdia quelen). Three hundred juveniles (initial mean weight 17.35 ± 0.97 g) were fed for 90 days with diets containing increasing levels of a probiotic additive (0.15, 0.30, 0.45 and 0.60 g/kg of feed), which consisted of a blend between Bacillus subtilis and B. cereus, both at a concentration of 4 × 1011 CFU/g, and a control diet without the additive. In males, the presence of the probiotic had an effect on relative seminal volume, sperm cells’ survival, gonadosomatic, hepatosomatic and viscerosomatic indexes, as well as transpose beat frequency, displacement velocity, motility rate and straightness of sperm cells. In females, the probiotic inclusion resulted in presented better in spawning and fertilization rates, viscerosomatic fat accumulation and development of germ cells. Additionally, the hepatic integrity and hepatocyte developmental characteristics were preserved by the presence of the probiotic additive. Thus, the inclusion of 0.60 g/kg of the probiotic could be recommended for the improvement of the reproductive performance of R. quelen.
Keywords: broodstock; feed additives; native species; seminal quality; viable oocytes